Atherosclerosis regression and high-density lipoproteins. - Lee, J; Choudhury, R (2010)
Atherosclerosis regression has been demonstrated clearly in animal experimental models and, to a lesser extent, in human clinical studies. Imaging techniques for study of the arterial wall are playing a key role in promoting our appreciation of regression. LDL lowering remains the mainstay of current lipid treatment, but given the multiple antiatherosclerotic functions of HDL, including reverse cholesterol transport, agents that target HDL may represent the next generation of treatment for atherosclerotic disease. Currently available agents, including nicotinic acid, have documented antiatherosclerotic effects and trials examining clinical outcomes in the context of contemporary LDL treatment are now underway. Future approaches to HDL treatment may include cholesteryl ester transfer protein inhibitors and apolipoprotein A-I mimetics.